Intellectual enthusiasm, a playground, God’s work: understanding contractors’ rationales in International Large-Scale Assessment (ILSA) contracts - Addey, Camilla (Revista Española de Educación Comparada, 2022)
Why are contractors keen to develop, implement, and analyse International Large-Scale Assessments (ILSAs) when they appear to make no financial gains? What makes ILSA contracts so attractive? This paper takes as its starting point the fact that almost all ILSA contractors interviewed stated their ILSA work is an investment, either in the form of a break-even or a loss contract. Applying policy borrowing and lending theory to non-state actors, and analysing 35 interviews with OECD and IEA staff and ILSA contractors, the paper discusses why contractors carry out ILSA contracts or donate to ILSAs. Rationales relate to interests in methodological developments and innovation; research; social responsibility; learning; exposure; prestige; credibility; networks; business opportunities; and individual rationales. The paper identifies parallels with the motives of corporate philanthropy in education. The paper concludes that ILSA contractors are using ILSAs to forward their political agendas, which include growing the learning assessment market.